LATIHAN SKIPPING TERHADAP DAYA LEDAK DALAM GERAKAN SMASH PERMAINAN BOLA VOLI PESERTA DIDIK SMA - Arianto, Deni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The problems discussed in this study is Is skipping exercise influence on the movement of explosive power smash volleyball games learners SMA Negeri 9 Pontianak. The purpose of this study was to determine the effect of skipping training on explosive power in smash movement volleyball games learners SMA Negeri 9 Pontianak. The research method experiment involving two variables: skipping exercise independent variables and the dependent variable is explosive power in smash movement volleyball games. The population in this study were students of SMA 9 Pontianak amounting to 24 students, the sampling using total sampling method, which means that all populations to be taken all sempel, with a sample size of 24 students. This research technique using test and measurement, a test with a grating instrument leg muscle explosive power with power vertical jump. Data analysis using t-test formula. These results indicate there are significant skipping exercise to smash the movement of explosive power in a game of volleyball students SMA Negeri 9 Pontianak. This can be evidenced by the results of the calculation, where the value ttest is 4,534> t table value (1.714), so the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Keywords: Skiipping, explosive power spike a volleyball